2015
DOI: 10.4103/2229-3485.154009
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and challenges in researches by Iranian students of medical universities

Abstract: Background:Health sciences research (HSR) is an essential part of improving health care which plays a critical role in the field of medicine and clinical practice. The aim of the current study was to assess barriers to the research by students of medical sciences as well as to find out effective strategies for management of student researches in Iranian universities.Materials and Methods:This study utilized a hybrid design with quantitative and qualitative analytical approaches conducted on 627 students in six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Examples include lack of funds [57]), insufficient access to electronic resources [58], constrained availability of the internet [57,59] and sometimes, even war/conflicts [57]. …”
Section: Discussionmentioning
confidence: 99%
“…Examples include lack of funds [57]), insufficient access to electronic resources [58], constrained availability of the internet [57,59] and sometimes, even war/conflicts [57]. …”
Section: Discussionmentioning
confidence: 99%
“…Only 20% of undergraduate student say there is no adequate time to do research during medical school, medical student suffering from lack of training and guidance with research supervisors ( 4 ). And many studies said that the early participation in the research will promotes a tendency to keep going research in their later life ( 5 ). Even if medical students do not participate to practice clinical research, research knowledge will improve their ability to make evidence based decisions in their clinical life ( 6 ) studies have showing that students in developing countries face more barriers in conducting research than students in developed countries ( 7 ) some studies show that 43.9% of student had positive attitude toward research ( 8 ) and 34.4% was conducting research and only 17.4% of them had published in journals ( 9 ) and some studies said that there is no difference in the extent of research participation among students from different high school backgrounds ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have demonstrated awareness of the importance of research in dentistry among dental students (11)(12)(13). The majority of Medical students in their undergraduate period are interested in conduct research, but unfortunately, there are some barriers and challenges that prevent them from doing it (5). Limited level of knowledge to conduct research and very low practice are considered barriers.…”
Section: Introductionmentioning
confidence: 99%
“…Our result ndings showed that institutional barriers were the fourth most crucial barrier to effective medical student research. Previous studies cited institutional barriers as the most important and main barrier to research [38,39,40]. Inadequate payment for research-related activities was the signi cant institutional barrier that reduces medical students' motivation to engage in research activities.…”
Section: Discussionmentioning
confidence: 99%